1991
DOI: 10.1002/ana.410290511
|View full text |Cite
|
Sign up to set email alerts
|

Lhermitte‐duclos disease and cowden disease: A single phakomatosis

Abstract: Two unrelated patients with macrocephaly, seizures, and mild cerebellar signs had a dysplastic gangliocytoma of the cerebellum (Lhermitte-Duclos disease). Both also had autosomal dominant Cowden disease as evidenced by facial, oral, and acral papules. In the two families, 9 sibs demonstrated the mucocutaneous lesions, thyroid disease, breast tumors, and ovarian tumors compatible with the diagnosis of Cowden disease. Some of the sibs also showed various degrees of neurological signs such as macrocephaly, mental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
81
0
5

Year Published

1992
1992
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(89 citation statements)
references
References 14 publications
3
81
0
5
Order By: Relevance
“…However, the systematic ascertainment and characterisation of head circumference has not been performed in CS or BRRS nor in the molecularly defined PHTS. Furthermore, while it is presumed that the aetiology of the macrocephaly is megencephaly from single case-report imaging, 11 we do not know if this is the case. Therefore, we sought to systematically measure and characterise the OFC from our adult and paediatric research participants found to have germline pathogenic PTEN mutations.…”
Section: Introductionmentioning
confidence: 90%
“…However, the systematic ascertainment and characterisation of head circumference has not been performed in CS or BRRS nor in the molecularly defined PHTS. Furthermore, while it is presumed that the aetiology of the macrocephaly is megencephaly from single case-report imaging, 11 we do not know if this is the case. Therefore, we sought to systematically measure and characterise the OFC from our adult and paediatric research participants found to have germline pathogenic PTEN mutations.…”
Section: Introductionmentioning
confidence: 90%
“…8,9 Megalencephaly and LDD are the most important neurological features of CD and the cause of symptoms like tremor, ataxia, and mental retardation. [8][9][10] In addition to these benign symptoms, CD patients have an increased risk of developing malignancies. They include follicular cell carcinoma of the thyroid, carcinomas of the breast and malignant cancers of the urogenital and digestive tract.…”
Section: Introductionmentioning
confidence: 99%
“…The most characteristic lesions are multiple facial trichilemnomas, acral keratosis and multiple oral papillomas, occurring in 99% of CD patients (1 -4). Lhermitte-Duclos disease (LDD), characterized by a dysplastic gangliocytoma of the cerebellum, leading to progressive cerebellar syndrome and frequent hydrocephaly, is now established as a component of CD (5)(6)(7)(8).…”
Section: Letter To the Editormentioning
confidence: 99%
“…Megencephaly/macrocephaly is present in 38% of CD patients and 80% of LDD patients (4,6,7). CNS tumors, both malignant and benign, may also be components of CD.…”
Section: Letter To the Editormentioning
confidence: 99%